ChemInform Abstract: Chemistry of 3‐(1H‐Indol‐3‐yl)‐3‐oxopropanenitrile. Issue 29 (22nd July 2014) - Fadda, Ahmed A.; El‐Mekabaty, Ahmed; Mousa, Ibrahim A.; Elattar, Khaled M.
Abstract Review: 69 refs.